Adsorption isotherm of deoxyadenosine under the conditions of a reverse phase liquid chromatography - Polunina, IA; Choi, DK; Row, KH; Larin, AV (MAIK NAUKA/INTERPERIODICA, 1996)
Adsorption isotherm of deoxyadenosine from a water-enriched mixture of water and methanol on silica gel with reverse C-18 phases was measured using high-performance chromatography. It was shown that at low concentrations (within the range of 0.1 to 10 mu g/cm(3)) the adsorption isotherm is most satisfactorily approximated by the Freundlich equation. Analysis of the data available on thymine adsorption confirms that the Freundlich equation may be employed in the range of low concentrations to approximate the isotherm of adsorption on silica gel with reverse phases in the case of water-enriched mobile phases.
Keywords: SOLUTE